Beliefs About the Future – How What Will Have Been Decides on How We Are Justified - NEUMANN, Saskia Janina (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
The importance of the justification of our beliefs is a long-debated question. The question of how our memory beliefs are justified, however, is a question we have usually neglected as our memory does not seem to draw much attention to itself. As long as it works, we do not even notice that we use it most of the time. In my opinion, the question of how our memory beliefs are justified, however, should play a bigger role in the philosophical debate. The reason for this claim is that most of our beliefs are memory beliefs. A position, I will argue for in this paper. Based on empirical findings in Cognitive Science, I will explain that our memory is not only involved in forming beliefs about the past but more controversially in forming beliefs about the present, in reasoning processes and even more controversially in forming beliefs about the future. If beliefs about what has been, about what is the case in the present and even about what will have been the case in the future are memory beliefs, reconsidering our strict focus on the justification of mere beliefs seems to be a change in debate worth considering.